A non-standard monetary policy shock: the ECB's 3-year LTROs and the shift in credit supply - Matthieu Darracq Pariès; Roberto A. De Santis (European Central Bank (ECB), 2013)
The identification of non-standard monetary policy shocks is a key challenge for econometricians, not least as these measures are somewhat unprecedented in modern central banking history and as the instruments vary widely across the various non-standard measures. This paper focuses on the 3-year long-term re-financing operations (LTROs), implemented by the ECB in December 2011 and February 2012. The macroeconomic impact of this measure is identified using the April 2012 Bank Lending Survey (BLS) as well as the special ad-hoc questions on the LTROs conducted in mid-February 2012. We estimate a panel-VAR for the euro area countries, which include relevant BLS variables, and identify credit supply shocks both recursively and with sign restriction methods. The macroeconomic effects of the 3-year LTROs are associated with the favorable credit supply shocks extracted through BLS information for the first half of 2012. Compared with the most likely developments one could have expected at the end of 2011 when financial tensions culminated, our counterfactual exercises suggest that the 3-year LTROs significantly lifted prospects for real GDP and loan provision to non-financial corporations over the next two-to-three years.
Keywords: C23; E52; 330; Non-standard monetary policy measures; Panel VAR